STRUCTURE AND MORPHOMETRY OF BALI DUCK PANCREAS IN THE GROWER PHASE - I Gde Andhika Putra Pratama; Ni Luh Eka Setiasih; Sri Kayati Widyastuti; Ni Ketut Suwiti; Ni Nyoman Werdi Susari; I Ketut Suatha (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
The pancreas is part of the digestive system which acts as a digestive aid organ. The pancreas has two functions, namely exocrine and endocrine. This study aims to determine the structure and morphometry of the pancreas of Bali ducks (Anas Sp) of different sexes in the growing phase. This research used 18 Balinese ducks which were divided into 2 groups, namely male and female with 9 each (3 months old). The method for examining anatomical structures is carried out by direct observation and histological structures using a binocular light microscope. Morphometry was measured using calipers for length and width, scales for pancreatic weight, and measuring cups for volume. Histomorphometry was measured using the Olympus cellSens Standard application. The results of the anatomical and histological structure data were analyzed using qualitative descriptive analysis, while the morphometric data used the Independent Sample T-Test. The anatomical structure of the Bali duck pancreas is flat like a lobed tongue and pink in colour, consisting of a capsule, islets of Langerhans, acini, intercalary ducts, intralobular ducts, interlobular ducts, intralobular septa, interlobular septa, veins and arteries. The results of morphometric measurements of Bali duck pancreas showed significant differences (P<0.05) in the weight and volume of the pancreas. Histomorphometric measurements of the area of the islets of Langerhans, the area of the acini, the thickness of the intralobular septa, and the thickness of the interlobular septa showed that they were not significantly different (P>0.05) in both sexes. The anatomical structure and histology of the pancreas of male and female Bali ducks are the same, but there are differences in morphometry